2012
DOI: 10.1175/jhm-d-12-07.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Scale Characteristics of Precipitation Simulated by Regional Climate Models and the Implications for Hydrological Modeling

Abstract: Precipitation simulated by regional climate models (RCMs) is generally biased with respect to observations, especially at the local scale of a few tens of kilometers. This study investigates how well two different RCMs are able to reproduce the spatial correlation patterns of observed summer precipitation for the central United States. On local scales, gridded precipitation observations and simulated precipitation are compared for the period of the 1987 First International Satellite Land Surface Climatological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 80 publications
2
23
0
Order By: Relevance
“…The long-term and high-resolution tree-ring records presented here can provide useful proxy information addressing this data gap. In addition, the low-frequency variability from the 11-year smoothed series is important for local climate change research, since this would be the foundation for sound regional climate modeling and for more reliable forecasts of trends in future precipitation variability in the cold and arid Qilian Mountains, similarly to equivalent studies in different regions [72][74].…”
Section: Discussionmentioning
confidence: 99%
“…The long-term and high-resolution tree-ring records presented here can provide useful proxy information addressing this data gap. In addition, the low-frequency variability from the 11-year smoothed series is important for local climate change research, since this would be the foundation for sound regional climate modeling and for more reliable forecasts of trends in future precipitation variability in the cold and arid Qilian Mountains, similarly to equivalent studies in different regions [72][74].…”
Section: Discussionmentioning
confidence: 99%
“…Model domains and analysis area. Figure from Rasmussen et al () ©American Meteorological Society, used with permission…”
Section: Examplesmentioning
confidence: 99%
“…To achieve this, we apply a convolution procedure that smooths the field before thresholding the data. For unforced convection, Rasmussen et al (2012) studied how well spatial correlation patterns of summer precipitation for the central United States were simulated by two RCMs. They showed that the models and observations were more strongly correlated when compared on larger scales, and their main conclusion was that model precipitation should be compared with observations on scales of at least around 100 km.…”
Section: Evaluation Datamentioning
confidence: 99%